2010
DOI: 10.1093/humupd/dmq001
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose tolerance, type 2 diabetes and metabolic syndrome in polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: BACKGROUND Polycystic ovary syndrome (PCOS) is a common condition in reproductive-aged women associated with impaired glucose tolerance (IGT), type 2 diabetes mellitus (DM2) and the metabolic syndrome. METHODS A literature search was conducted (MEDLINE, CINAHL, EMBASE, clinical trial registries and hand-searching) identifying studies reporting prevalence or incidence of IGT, DM2 or metabolic syndrome in women with and without PCOS. Data were presented as odds ratio (OR) [95% confidence interval (CI)] with fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
498
3
22

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 903 publications
(537 citation statements)
references
References 111 publications
14
498
3
22
Order By: Relevance
“…(5,6). The different prevalence of obesity in the clinical series of women with PCOS almost certainly reflects the overall rates of obesity (30-70%) in different populations (24,25,26).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 2 more Smart Citations
“…(5,6). The different prevalence of obesity in the clinical series of women with PCOS almost certainly reflects the overall rates of obesity (30-70%) in different populations (24,25,26).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…In adult overweight or obese PCOS women, menstrual abnormalities and chronic oligo-anovulation are more frequent, and the degree of hyperandrogenemia tends to be worse than in normal-weight women (29). It is of importance that longitudinal studies have shown that insulin resistance may worsen over time in obese PCOS women (30), and obesity per se is the major risk factor for the early development of T2D (5,6).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…PCOS is characterized by polycystic ovaries, oligoamenorrhea, and hyperandrogenism. It is associated with maternal obesity (3), insulin resistance (4), metabolic syndrome and type II diabetes (5,6), dyslipidemia (4), endometrial cancer, and possibly cardiovascular diseases later in life (4). Increased prevalence of pregnancy complications and adverse pregnancy outcomes is reported in PCOS women (7).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis showed that women with PCOS were four times more likely to develop T2DM compared with BMI-matched controls (10). Insulin resistance is proposed as a key pathophysiological feature of PCOS contributing to reproductive, cardiovascular and metabolic disturbances.…”
Section: Introductionmentioning
confidence: 99%